(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The study of subjects of the cycle of natural sciences among students forms an idea of the unity of nature. However, the existing school programs assume the assimilation of a large number of concepts that function as separate elements of knowledge. Therefore, various types of learning technologies are used in the educational process to solve certain problems and achieve planned learning results. In the process of teaching subjects of the natural science cycle, it is necessary to use new types of teaching technologies, such as the organization of integrated lessons. The integration of natural science subject groups makes it possible to solve the issue of complex study and formation of knowledge about biological processes, resulting in the idea of knowledge integration. One of the ways to develop the teachers’ skills in organizing integrated learning is proper planning and analysis of the lesson. In this article, we offer lesson structure and analysis forms as a means of increasing the effectiveness of planning and conducting an integrated lesson. Integrated lesson plans were drawn up using the proposed forms, which were tested in a number of schools in Shirak region. In order to ensure the effectiveness of the conducted integrated lessons and to implement further improvement, after each lesson, an analysis was carried out by the teacher and other specialists, noting its strengths and weaknesses. This analysis also allows to properly organize and improve the integrated lesson. According to the feedback from teachers and students, the integrated lessons tested in the above mentioned schools turned out to be quite effective, and the proposed forms were useful.